2009
DOI: 10.1590/s0100-29452009000400014
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica populacional da mosca-negra-dos-citros Aleurocanthus woglumi ashby (hemiptera: aleyrodidae) em Citrus spp. no município de São Luís - MA

Abstract: RESUMO-O objetivo deste trabalho foi avaliar a dinâmica populacional de Aleurocanthus woglumi ao longo de um ano, verifi cando-se a época de maior ocorrência, seus picos populacionais e a distribuição dessa praga em dois pomares de Citrus spp. no município de São Luís -MA. Para o estudo da dinâmica populacional, foram selecionadas 10 plantas ao acaso, em cada pomar, coletando-se 20 folhas por planta, no período de julho de 2006 a junho de 2007, contando-se o número de posturas, ovos e ninfas. Para a determinaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…According to Medeiros et al (2009) and Silva et al (2011a), citrus black-fly occurs in all months of the year with population peaks, concentrating on periods of low rainfall, a fact observed in the period from August to October 2010 in the municipality of Capitão Poço. These results favor the planning and execution of operational measures that are more feasible and safe for the control of these aleyrodidae within the principles of integrated pest management (IPM).…”
Section: Resultsmentioning
confidence: 99%
“…According to Medeiros et al (2009) and Silva et al (2011a), citrus black-fly occurs in all months of the year with population peaks, concentrating on periods of low rainfall, a fact observed in the period from August to October 2010 in the municipality of Capitão Poço. These results favor the planning and execution of operational measures that are more feasible and safe for the control of these aleyrodidae within the principles of integrated pest management (IPM).…”
Section: Resultsmentioning
confidence: 99%
“…FLandErS (1969), em trabalho realizado no México, observou que ventos fortes e chuvas pesadas mostraram-se capazes de desalojar e matar adultos da mosca-negra-doscitros. Mesmo resultado encontrado por MEdEIroS et al (2009), estudando em condições de campo a dinâmica populacional da mosca-negra-dos-citros em Citrus spp. no município de São Luís -MA, observaram que no período chuvoso houve redução no número de posturas, ovos, e ninfas nas áreas experimentais.…”
Section: Resultsunclassified
“…The variation in climatic variables, especially temperature and rainy season, is important on infestation potential of CBF [13]. In general, the highest population levels of CBF occur in the low-precipitation season [14,15]. But in Municipality of São José de Ribamar, State of Maranhão (Brazil), in a commercial orchard of C. latifolia, the average total number of citrus blackflies was higher during the rainy season than in dry season [16].…”
Section: Dynamics Populations and Dispersal Patternmentioning
confidence: 99%
“…However, in another experiment in State of Maranhão, Brazil, it was observed that during rain period the insects (eggs and nymphs) were distributed homogeneously on the trees canopies in a commercial orchard. In addition during the period without rain, the north and south quadrants showed less clutches/plant, eggs/plant and nymphs/plant in a non-commercial orchard and clutches/plant, eggs/plant in a commercial orchard [15]. The infestation level may vary in accordance with the crop system, because there is evidence that infestation of CBF is different in agroforestry and conventional system [13].…”
Section: Dynamics Populations and Dispersal Patternmentioning
confidence: 99%